2019
DOI: 10.1089/jamp.2018.1517
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Submicron Particle Paclitaxel (NanoPac) Induces Tumor Regression and Immune Cell Infiltration in an Orthotopic Athymic Nude Rat Model of Non-Small Cell Lung Cancer

Abstract: Background: This study evaluated the antineoplastic and immunostimulatory effects of inhaled (IH) submicron particle paclitaxel (NanoPac Ò) in an orthotopic non-small cell lung cancer rodent model. Methods: Male nude rats were whole body irradiated, intratracheally instilled with Calu-3 cancer cells and divided into six treatment arms (n ¼ 20 each): no treatment (Group 1); intravenous nab-paclitaxel at 5.0 mg/kg once weekly for 3 weeks (Group 2); IH NanoPac at 0.5 or 1.0 mg/kg, once weekly for 4 weeks (Groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…Evaluation of tumor tissues from these animals determined that IT NanoDoce administration resulted in high levels (> 1500 μg/g of tissue) of docetaxel within the tumor up to 50 days after treatment [1]. Further, we found that nebulized submicron particle paclitaxel (NanoPac®) substantially reduced or eradicated Calu-3 non-small cell lung cancer (NSCLC) tumors in immunocompromised mice which did not occur following IV administration of nab-paclitaxel [2,3]. These previous studies were performed in rodents with genetically depleted T cells, whereas here we evaluated the response of an intact immune system to direct injection of NanoDoce compared to IV docetaxel in a Renca syngeneic model.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Evaluation of tumor tissues from these animals determined that IT NanoDoce administration resulted in high levels (> 1500 μg/g of tissue) of docetaxel within the tumor up to 50 days after treatment [1]. Further, we found that nebulized submicron particle paclitaxel (NanoPac®) substantially reduced or eradicated Calu-3 non-small cell lung cancer (NSCLC) tumors in immunocompromised mice which did not occur following IV administration of nab-paclitaxel [2,3]. These previous studies were performed in rodents with genetically depleted T cells, whereas here we evaluated the response of an intact immune system to direct injection of NanoDoce compared to IV docetaxel in a Renca syngeneic model.…”
Section: Introductionmentioning
confidence: 90%
“…Prior to the point where group MTV = 2000 mm 3 , two treatment-related (TR) deaths occurred: one animal in the docetaxel-2°group was found dead on Day 6 and one animal on Day 18 in the IT/PT NanoDoce-2 group was euthanized on Day 18 due to severe BW loss. In IT NanoDoce-treated animals maintained on study beyond when control group MTV > 2000 mm 3 , one IT NanoDoce-2 was euthanized on Day 28 due to BW loss. Several animals across various treatment groups had similar necropsy findings of enlarged spleen and pale liver, kidneys and lungs at study endpoint (TV > 2000 mm 3 ).…”
Section: Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…William Johnston 1 , James Verco 1 , Gere diZerega 1,2 , Michael Frost 5 , Michael Baltezor 2,3 , Philip Kuehl 4…”
mentioning
confidence: 99%
“…1 US Biotest, Inc., San Luis Obispo, CA, USA; 2 Nanology, LLC., Fort Worth, TX, USA; 3 CritiTech, Inc., Lawrence, KS, USA; 4 Lovelace Biomedical, Albuquerque, NM, USA; 5 Western Diagnostic Services Laboratory, Santa Maria, CA, USA 19.9 5,800 23,112…”
mentioning
confidence: 99%